2017
DOI: 10.22159/ijpps.2017v9i6.18676
|View full text |Cite
|
Sign up to set email alerts
|

Application of the New Oroslippery Technology in the Preparation of Enteric Slippery Coated Tablet of Naproxen

Abstract: Objective: The aim of this study was to formulate enteric coated oroslippery tablets (OSTs) of naproxen to overcome the common problems of stomach irritation and swallowing difficulties which accompanied the administration of naproxen tablets.Methods: Different formulas of enteric slippery tablets were prepared by direct compression method. Various parameters were investigated like the effect of eudragit L-100 (eud.) concentration (as an enteric polymer), coating level and effect of different concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…7) revealed that a significant increase in taste masking in coated tablets (T1-T6) than the non-coated core tablet, because coating the tablet created a physical barrier between the drug and taste buds, In addition, the use of mannitol and peppermint oil resulted in a fine sweet taste, sense of coolness and freshness within the mouth [29,30]. Furthermore, the results showed a significant increase (p<0.05) in taste masking at the higher concentration of Kollicoat IR represented in T5 (19% Kollicoat) comparing to T1 with (9% Kollicoat) and T3 with (14% Kollicoat), in addition the results showed that double coating which represented in T2, T4, and T6 formulas, have a significant improvement(P<0.05) in the in vivo taste masking effect comparing to monolayer coating in T1,T3, and T5, respectively, these results might be due to the greater viscosity of the coating dispersion that observed by the higher Kollicoat concentrations in T6 which increased the hydrodynamic drag of the coating dispersion that finally gave a higher coat thickness [3].…”
Section: In Vivo Slipperiness and Taste Masking Effect Of The Preparementioning
confidence: 84%
See 2 more Smart Citations
“…7) revealed that a significant increase in taste masking in coated tablets (T1-T6) than the non-coated core tablet, because coating the tablet created a physical barrier between the drug and taste buds, In addition, the use of mannitol and peppermint oil resulted in a fine sweet taste, sense of coolness and freshness within the mouth [29,30]. Furthermore, the results showed a significant increase (p<0.05) in taste masking at the higher concentration of Kollicoat IR represented in T5 (19% Kollicoat) comparing to T1 with (9% Kollicoat) and T3 with (14% Kollicoat), in addition the results showed that double coating which represented in T2, T4, and T6 formulas, have a significant improvement(P<0.05) in the in vivo taste masking effect comparing to monolayer coating in T1,T3, and T5, respectively, these results might be due to the greater viscosity of the coating dispersion that observed by the higher Kollicoat concentrations in T6 which increased the hydrodynamic drag of the coating dispersion that finally gave a higher coat thickness [3].…”
Section: In Vivo Slipperiness and Taste Masking Effect Of The Preparementioning
confidence: 84%
“…The volunteers were told to roll the tablet gently in their oral cavity without chewing or biting; whenever a slight taste of bitterness can be detected the volunteered were informed to spit the tablet out along with the saliva and to rinse their mouth immediately. The time required for bitterness sensation was recorded and considered as an indicator for taste masking property for the prepared RHCl OSTs [3].…”
Section: In Vivo Evaluation Of Slipperiness and Taste Masking Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of ASA enteric-coated tablets The enteric-coated tablets for delayed-release have these steps [10,11].…”
Section: Preparation Of Tabletsmentioning
confidence: 99%
“…The spectra FT-IR supports in comparing with a standard FT-IR spectrum of the pure drug to detect any physicochemical incompatibility between the drug and different excipients. 28…”
Section: Drug-excipients Compatibility Study and Identification Fourimentioning
confidence: 99%